THE HISTORY OF THE FORMATION OF POPULAR CULTURE AND ITS TYPES: COUNTERCULTURE, SUBCULTURE, POPULAR CULTURE, SCREEN CULTURE - Boratov Shavkat; J. SH. Mustafayev (Лучшие интеллектуальные исследования, 2024)
Abstract: A study of the topic of popular culture, showing its powerful influence in society and how it is connected to people's lives, attitudes and cultural values. How Popular Culture can be used in the teaching and learning of cultural concepts is embodied in this article.